Cultural dimension of individualism and collectivism and its perceptual and cognitive correlates in cross-cultural research - Čeněk, Jiří (Journal of Education Culture and Society, 2020)
This paper reviews the current findings on the dimension of individualism/collectivism, which might be a useful tool for the comparison of different cultures and for the investigation of the effect of culture as a psychological concept on individual mental processes. The validity and reliability of the concept of the dimension of individualism/collectivism is discussed. The related theory of analytic and holistic thinking is introduced within a framework of extensive comparative research in the field of cross-cultural psychology. Several interesting research designs on cross-cultural differences in cognition and perception are described. The empirical part contains a short report of research conducted on a sample (N=92) of Czech and Czech Vietnamese university students using a scale of horizontal and vertical individualism/collectivism (Bartoš, 2010). The results do not fully support the traditional view of individualistic Europeans and collectivistic Asians.